A cause of new onset isolated right heart failure in sixtyfive years old patient: Ebstein anomaly - Velibey, Yalçın; Altay, Servet; Çakmak, Hüseyin Altuğ; Keleş, İbrahim; Karadağ, Nalan; Çağdaş, Metin; Uluganyan, Mahmut (Cerrahpaşa Medical Journal, 2019)
Sixty five years old male with an unknown cardiac history was admitted to our clinic with two months of weakness, fatigue, leg and abdominal swelling. Electrocardiography findings were normal except P pulmonale in inferior derivations. Telecardiography showed normal cardiothoracic ratio. Transthoracic echocardiography revealed pulmonary artery pressure 40 mmHg, normal left ventricular wall thickness, normal size and functions with an enlarged right atrial cavity (58 mm), decreased right ventricular size (30 mm), and mild tricuspid regurgitation. Also, cardiac magnetic resonance showed pathologic findings which were consistent with Ebstein anomaly. The coronary angiography showed normal coronary arteries. Here, we report a sixty five years old patient with new onset isolated right heart failure due to Ebstein anomaly.